Vitamin D and the occurrence and treatment of periodontitis – review of literature - Brzeska, Magdalena; Mazurek-Mochol, Małgorzata; Dembowska, Elżbieta (Journal of Stomatology, 2017)
Periodontal disease (periodontitis) is a multifactorial inflammatory disease that affects the tissues of the periodontium surrounding the teeth and is the leading cause of tooth loss in the elderly. There is evidence that the most active form of vitamin D, i.e. 1,25-hydroxyvitamin D (calcitriol) – an important factor affecting the endocrine function of the body – may affect the development of chronic inflammation in tissues. The papers presented in this review indicated a significant association between vitamin D in blood serum and parameters such as clinical attachment level (CAL), periodontal pocket depth (PD), and bleeding on probing (BOP). Moreover, both 25(OH) D and 1,25(OH)D decrease expression of IL-8, an important pro-inflammatory cytokine participating in the development of periodontitis. Studies on genetic polymorphisms of the vitamin D receptor-encoding gene (VDR) have shown an increased risk of chronic periodontitis (ChP) and a reduced risk of aggressive periodontitis (AgP) in patients inheriting specific genotypes. Research on the occurrence of the vitamin D binding protein (DBP) found that patients with generalized aggressive periodontitis have higher levels of DBP in serum, but lower levels of DBP in the gingival crevicular fluid. This paper presents scientific works discussing the decrease in pocket depth (PD), reduction of bleeding on probing (BOP), gingival index (GI), loss of clinical attachment level (CAL), and loss of the alveolar bone level (BL) following supplementation with vitamin D in specified doses.